1988
DOI: 10.1038/clpt.1988.207
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol for the control of hypertension after neurologic surgery

Abstract: We sought to evaluate the effectiveness of esmolol vs placebo in 40 patients emerging from general anesthesia for neurosurgery. Efficacy was defined as a decrease in systolic blood pressure to within 20% above average ward pressure. The need for additional antihypertensive agents to control blood pressure was also used to define efficacy. During the infusion period 20 of 21 (95%) of the esmolol-treated patients and two of 19 (11%) of the patients receiving placebo had return of systolic blood pressure to withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…15 trials achieved a mean heart rate of 75 beats per min or less at study end in the β-blocker group, [3][4][5][6]25,28,31,32,34,36,37,43,45,46,50 whereas in nine trials the mean heart rate was greater than 75 beats per min. 23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…15 trials achieved a mean heart rate of 75 beats per min or less at study end in the β-blocker group, [3][4][5][6]25,28,31,32,34,36,37,43,45,46,50 whereas in nine trials the mean heart rate was greater than 75 beats per min. 23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 99%
“…Five trials enrolled high surgical-risk patients (emergency surgery, vascular surgery), 3,5,27,32,40 five enrolled intermediate-risk or high surgical-risk patients, 4,6,28,30,38 22 enrolled intermediate surgical-risk patients (intrathoracic, intraperitoneal, carotid endarterectomy, head and neck, orthopedic, or prostate surgery), [22][23][24][25][26]31,[33][34][35][36][37]39,[41][42][43][44][45][46][47][48][49][50] and one enrolled low surgical-risk patients. 29 A sensitivity analysis on the basis of surgical risk categories showed a 63% decreased risk of all-cause mortality and a 44% decreased risk of non-fatal myocardial infarction in trials with high surgical risk (tables 2 and 3); this finding was driven largely by the trial by Poldermans and colleagues.…”
Section: Weight (%)mentioning
confidence: 99%
“…We excluded nine studies which reported only major cardiovascular complications within 30 days of surgery [1,2,[21][22][23][24][25][26][27] and a further nine studies which did not present data on perioperative myocardial ischaemia [28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Esmolol has been used successfully for hypertension in the perioperative period (Cucchiara et al 1986; Girard et al 1986; Newsome et al 1986; Gray et al 1987; Gibson et al 1988). The metabolism of esmolol is via rapid hydrolysis of ester linkages by red blood cell (RBC) esterases and is not dependant on renal or hepatic function.…”
Section: Pharmacotherapymentioning
confidence: 99%